Partially fluorinated derivatives as a powerful tool for the restoration of blanched easel paintings - Zhang, Yuqing; Eveno, Myriam; Gallier, Florian; Lattuati-Derieux, Agnès; Lubin-Germain, Nadège; Camaiti, Mara; Salvini, Antonella (Progress in organic coatings, 2025)
The use of specific coatings has considerable importance in the field of cultural heritage conservation. The blanching of easel paintings is a worrying phenomenon induced by excessive humidity and porous structures, often obscuring the image beneath a white haze. The research available in the literature describing solutions to solve this problem is extremely limited. In this research, new oligoamides containing hydroxyl and/or amino groups, i.e., partially fluorinated oligodiethylene succinamide-l-tartaramide (DSTF) and oligodiethylene succinamide (DSF), were designed to give high affinity with the polar components present in paint films through non-covalent interactions, and have reduced environmental impact compared to the previously proposed perfluoroamide (DC6G900). These innovative products represent one of the few solutions proposed for this area of application. Their syntheses were carried out via condensation and subsequently ring-opening reaction of the short-fluorinated epoxy compound, 3-perfluorohexyl-1,2-epoxypropane (EC6F). The short-fluorinated chain has a dual effect; it improves surface performance by lowering surface tension while simultaneously reducing environmental impact compared to the perfluoro source previously used. The performance of the two new fluorinated oligoamides (DSTF, DSF) on blanched easel paintings was investigated through a series of tests, from the macroscopic to the microscopic scale. The new fluorinated oligoamides dramatically decreased the luminance value (almost restoring the value of the un-blanched sample) in comparison with the other tested compounds (ESTF, ESF, DF and DC6G900 as a reference). This result is ascribed to the ability of the compounds to fill the pores of the blanched surfaces, as demonstrated by the morphological study using a Field emission gun - Scanning electron microscopy. In addition, preliminary investigations showed that all the tested compounds, can be removed from the treated mock-ups using 2-propanol or 2,2,2-trifluoroethanol, giving promising results concerning the removal of the restoration treatments. [Display omitted] •New partially fluorinated oligoamides easy synthesized by two steps reaction•The new oligoamides have proven to be effective for blanched paintings restoration•The new oligoamides have reduced environmental impact compared to perfluoro compounds•FEG-SEM study proved their ability to fill the pores that cause the blanching effect